Graphene-based topological insulator with an intrinsic bulk band gap above room temperature - Kou, Liangzhi; Yan, Binghai; Hu, Feiming; Wu, Shu-Chun; Wehling, Tim O.; Felser, Claudia; Chen, Changfeng; Frauenheim, Thomas (Nano Letters, 2013)
Topological insulators (TIs) represent a new quantum state of matter characterized by robust gapless states inside the insulating bulk gap. The metallic edge states of a two-dimensional (2D) TI, known as the quantum spin Hall (QSH) effect, are immune to backscattering and carry fully spin-polarized dissipationless currents. However, existing 2D TIs realized in HgTe and InAs/GaSb suffer from small bulk gaps (<10 meV) well below room temperature, thus limiting their application in electronic and spintronic devices. Here, we report a new 2D TI comprising a graphene layer sandwiched between two Bi 2Se3 slabs that exhibits a large intrinsic bulk band gap of 30-50 meV, making it viable for room-temperature applications. Distinct from previous strategies for enhancing the intrinsic spin-orbit coupling effect of the graphene lattice, the present graphene-based TI operates on a new mechanism of strong inversion between graphene Dirac bands and Bi2Se 3 conduction bands. Strain engineering leads to effective control and substantial enhancement of the bulk gap. Recently reported synthesis of smooth graphene/Bi2Se3 interfaces demonstrates the feasibility of experimental realization of this new 2D TI structure, which holds great promise for nanoscale device applications. © 2013 American Chemical Society.
CRIS-Team Scopus Importer:2023-03-20
Keywords: band inversion; graphene; large bandgap; quantum well; strain engineering; Topological insulator